Polypropylene resin composition for inflation film, method for producing the same, inflation film, method for producing film, and package

The use of a polypropylene resin composition with a specific branched polypropylene resin and homopolymer propylene addresses the issues of strength and transparency in polypropylene films during high-speed inflation molding, resulting in improved film quality.

JP2025040487APending Publication Date: 2025-03-25JAPAN POLYPROPYLENE CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147320
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Polypropylene films produced by inflation molding face issues with insufficient strength and transparency when molding speed increases, leading to damaged surface quality when printed on.

Method used

A polypropylene resin composition containing a branched polypropylene resin with specific properties, combined with a homopolymer of propylene, is used to improve transparency and surface roughness without compromising film strength during high-speed inflation molding.

Benefits of technology

The composition achieves strain hardening and stress relaxation during high-speed inflation molding, suppressing periodic bubble vibrations and enhancing the transparency, surface roughness, or both of the resulting film without sacrificing strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040487000006
    Figure 2025040487000006
  • Figure 2025040487000007
    Figure 2025040487000007
  • Figure 2025040487000008
    Figure 2025040487000008
Patent Text Reader

Abstract

To provide a polypropylene resin composition capable of improving one or more of the transparency and surface roughness of a film produced by inflation molding, without impairing the strength of the film.SOLUTION: Provided is a polypropylene resin composition for an inflation film, which includes: a branched polypropylene resin (X) exhibiting characteristics (X-1) to (X-4), and a polypropylene resin (Y) exhibiting characteristics (Y-1) and (Y-2), the composition containing from 1 mass% to 80 mass% of the resin (X) and from 20 mass% to 99 mass% of the resin (Y), based on a total of 100 mass% of the resin (X) and the resin (Y).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polypropylene resin composition for an inflation film and a method for producing the same, an inflation film and a method for producing the film, and a package. [Background technology]

[0002] Patent Document 1 discloses a polypropylene film produced by air-cooling inflation molding, which contains a propylene-α-olefin random copolymer using a metallocene compound and a nucleating agent. Patent Document 2 discloses a polypropylene film produced by air-cooling inflation molding, which contains a propylene-α-olefin copolymer having a melting point of 110 to 155° C. using a metallocene compound and a polypropylene-based resin having a branched structure. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-182967 A [Patent Document 2] Patent Publication No. 2014-132068 Summary of the Invention [Problem to be solved by the invention]

[0004] However, polypropylene films produced by inflation molding using conventional technology had problems such as insufficient strength and low transparency when the molding speed was increased, and when printing was performed on the film, the surface roughness reduced the luxurious feel.

[0005] In view of the above-mentioned problems, an object of the present invention is to provide a polypropylene-based resin composition that improves the transparency, surface roughness, or a combination of these of a film produced by high-speed inflation molding without impairing the strength of the film, a method for producing the same, and an inflation film. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that by subjecting a polypropylene resin composition in which a branched polypropylene resin (X) having specific properties is contained in a polypropylene resin (Y) to high-speed inflation molding, it is possible to obtain an inflation film having improved transparency, surface roughness, or a combination of these properties without impairing the strength of the film, and have arrived at the present invention. The present invention relates to the following: <1> ~ <7> Regarding. <1> A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following properties (Y-1) to (Y-2), A polypropylene resin composition for an inflation film, comprising 1% by mass to 80% by mass of the resin (X) and 20% by mass to 99% by mass of the resin (Y), relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. Characteristic (Y-2): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.95 or more. <2> The polypropylene resin (Y) is a homopolymer of propylene. <1> The polypropylene resin composition according to claim 1. <3> A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A method for producing a polypropylene-based resin composition for an inflation film, comprising a step of dry-blending a polypropylene-based resin (Y) having the following properties (Y-1) to (Y-2): Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. Characteristic (Y-2): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.95 or more. <4> The above <1> or <2> An inflation film comprising the polypropylene resin composition according to claim 1. <5> The above <1> or <2> 2. A method for producing a film, comprising a step of molding the polypropylene resin composition according to claim 1 by an inflation method. <6> The inflation method is an air-cooled inflation method. <5> A method for producing the film according to claim 1. <7> The above <4> A package comprising the inflation film according to claim 1. Effect of the Invention

[0007] According to the present invention, there are provided a polypropylene-based resin composition that improves the transparency, surface roughness, or a combination of these of a film produced by high-speed inflation molding without impairing the strength of the film, a method for producing the same, and a film. The polypropylene resin composition of the present invention exhibits appropriate strain hardening and stress relaxation during high-speed inflation molding, and periodic bubble vibration is suppressed, so that the strength of the produced film is not impaired, and the transparency, surface roughness, or a combination of these can be improved. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a diagram illustrating the baseline and intervals of a chromatogram in GPC. [Diagram 2] FIG. 2 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for the branched polypropylene resins (X1) to (X3) used in the present invention and the reference branched polypropylene resins (CX1) to (CX3) are plotted. [Diagram 3] FIG. 3 is a diagram showing an example of an integrated molecular weight distribution curve. [Figure 4]1 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for branched polypropylene resins (X1) to (X3) used in the present invention and reference branched polypropylene resins (CX1) to (CX3) are plotted. [Diagram 5] FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum winding speed (MaxDraw) at 230° C., and data for the branched polypropylene resins (X1) to (X3) used in the present invention and the reference branched polypropylene resins (CX1) to (CX3) are plotted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] I. Polypropylene resin composition for inflation film The polypropylene resin composition for an inflation film of the present invention comprises a branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following properties (Y-1) to (Y-2), The resin (X) is contained in an amount of 1% by mass to 80% by mass and the resin (Y) is contained in an amount of 20% by mass to 99% by mass, relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. Characteristic (Y-2): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.95 or more.

[0010] The polypropylene resin composition of the present invention contains the branched polypropylene resin (X) having the above-mentioned properties (X-1) to (X-4), i.e., the specific branched polypropylene resin (X) having a specific molecular weight distribution and branching distribution and a high Ea corresponding to the MFR, and the polypropylene resin (Y) having the above-mentioned properties (Y-1) to (Y-2), and thus can improve the transparency, surface roughness, or a combination of these of a film produced by high-speed inflation molding without impairing the strength of the film.

[0011] The polypropylene resin (Y) has a MFR of 0.1 g / 10 min or more and less than 10 g / 10 min measured at a temperature of 230° C. and a load of 2.16 kg, and therefore contains many components with high molecular weights, and generally has high melt tension and rigidity, making it suitable for production by inflation molding. However, when the polypropylene resin (Y) is subjected to high-speed inflation molding alone, the transparency and surface roughness of the film tend to be insufficient, as shown in the comparative example described below. During high-speed inflation molding, the molten resin is usually continuously extruded from the die in a tubular shape, but the extruded molten tubular resin (bubble) tends to become unstable, vibrating, such as expanding and contracting like a balloon, until it is cooled and solidified (hereinafter, the instability of the molten tubular resin may be referred to as "bubble vibration"). If such bubble vibration occurs during inflation molding, the transparency and surface roughness of the resulting inflation film tend to be insufficient. In contrast, in the present invention, the polypropylene resin (Y) having the specific MFR is combined with the branched polypropylene resin (X) having the specific properties. The branched polypropylene resin (X) having the specific characteristics contains a multi-branched molecule having a molecular structure in which a large number of branch chains are introduced in the medium to high molecular weight region. On the other hand, it is a branched polypropylene resin that reduces ultra-high molecular weight components with extremely long relaxation times, and further has a favorable relationship between the flow activation energy (Ea) and MFR obtained by measuring dynamic viscoelasticity, which is an index of branching characteristics. The branched polypropylene resin (X) specified as above shows a relaxation time distribution in which many components have a relatively short relaxation time and few components have an extremely long relaxation time, that is, it has a moderate molecular weight distribution, so that strain hardening occurs and it is possible to improve the high-speed stretching characteristics. Therefore, the branched polypropylene resin (X) having the specific characteristics suppresses periodic bubble vibration during high-speed inflation molding, and affects the stabilization of the bubbles. Thus, when the branched polypropylene resin (X) is added to the polypropylene resin (Y) having the specific MFR, strain hardening occurs during high-speed inflation molding, periodic bubble vibration is suppressed, and the relaxation time of the stress caused by the round die during high-speed inflation molding is also shortened. Therefore, it is considered that the polypropylene resin composition of the present invention can improve the transparency, surface roughness, or a combination of these of a film produced by high-speed inflation molding without impairing the strength of the film.

[0012] The present invention will be described in detail below. In this specification, the use of "to" indicating a range of values ​​means that the values ​​before and after the range include the lower limit and upper limit. In this specification, the upper and lower limit values ​​of the numerical ranges may be arbitrarily combined, and the preferred ranges of the respective properties may be arbitrarily combined. In the present invention, logarithms are expressed in the common logarithm sense, ie, to the base 10. In the present invention, unless otherwise specified, the contents of the branched polypropylene resin (X) and the polypropylene resin (Y) in the resin composition are represented by mass ratios when the total mass of the branched polypropylene resin (X) and the polypropylene resin (Y) is taken as 100 mass%.

[0013] The polypropylene resin composition of the present invention contains the branched polypropylene resin (X) and the polypropylene resin (Y) having the properties (Y-1) to (Y-2) described above, in an amount of 1 to 80 mass% of the resin (X) and 20 to 99 mass% of the resin (Y), relative to 100 mass% of the total mass of the resin (X) and the resin (Y), and may further contain other components such as additives described later.

[0014] 1. Branched polypropylene resin (X) The branched polypropylene-based resin (X) used in the present invention may be a homopolymer of propylene, or a copolymer of propylene and one or more comonomers selected from α-olefin comonomers having 2 to 20 carbon atoms other than propylene, such as ethylene, 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene, etc. The branched polypropylene resin (X) used in the present invention may be a branched propylene polymer comprising propylene, ethylene, and 0 to 11 mol % of an α-olefin having 4 or more carbon atoms.

[0015] 1-1. Characteristics of branched polypropylene resin (X) Characteristics (X-1): The branched polypropylene resin (X) used in the present invention has a melt flow rate (MFR) of 0.1 g / 10 min to 100 g / 10 min measured at a temperature of 230° C. under a load of 2.16 kg in view of ease of inflation molding of the branched polypropylene resin composition. The MFR is preferably 1.0 g / 10 min or more, and may be 3.0 g / 10 min or more. On the other hand, the MFR is preferably 80 g / 10 min or less, more preferably 50 g / 10 min or less, and even more preferably 40 g / 10 min or less, and may be 30 g / 10 min or less. From the viewpoint of easily reducing the surface roughness of the film obtained by inflation molding, the MFR may be 25 g / 10 min or less, and may be less than 10 g / 10 min. In the present invention, the MFR is a value measured by pelletizing the branched polypropylene resin (X) and measuring the MFR at 230°C and a load of 2.16 kgf in accordance with JIS K7210-1:2014 "Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard test method". The pelletization is performed in the same manner as the "granulation" described in the examples below. The MFR of the branched polypropylene resin can be adjusted by (i) changing the temperature and / or pressure during polymerization of the polypropylene resin and / or (ii) adding hydrogen or other chain transfer agents to the monomers during polymerization of the polypropylene resin.

[0016] Characteristics (X-2): The branched polypropylene resin (X) used in the present invention has a ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) of 2.5 to 4.0 in view of ease of inflation molding of the branched polypropylene resin composition. Mz, Mw, and number average molecular weight (Mn) are each indices that represent the average molecular weight of a polymer. Mz is an index of the average molecular weight with a high specific gravity on the high molecular weight side, Mn is an index of the average molecular weight with a high specific gravity on the low molecular weight side, and Mw is an index of the average molecular weight in between. In addition, the respective ratios, Mw / Mn and Mz / Mw, are indices of the spread of the molecular weight distribution of the polymer.

[0017] In the branched polypropylene resin (X), from the viewpoints of the presence of an appropriate amount of a component having a long relaxation time and suppressing a decrease in melt tension, Mz / Mw is 2.5 to 4.0. The upper limit of Mz / Mw is preferably 3.6 or less, more preferably 3.4 or less, and even more preferably 3.2 or less. The lower limit of Mz / Mw is preferably 2.6 or more, more preferably 2.8 or more, and even more preferably 2.9 or more.

[0018] In addition, the branched polypropylene resin (X) used in the present invention may have a ratio of Mw to Mn (Mw / Mn) obtained by GPC of 3.0 to 7.0 in view of ease of inflation molding of the branched polypropylene resin composition. The upper limit of Mw / Mn may be 6.0 or less, 5.0 or less, 4.5 or less, or 4.3 or less. On the other hand, the lower limit of Mw / Mn may be 3.2 or more, or 3.3 or more. Furthermore, in view of the ease of inflation molding of the branched polypropylene resin composition, the Mw of the branched polypropylene resin (X) used in the present invention may be 150,000 to 350,000, 180,000 to 330,000, or 200,000 to 320,000.

[0019] The values ​​of Mz, Mw, Mn, Mw / Mn, and Mz / Mw are all obtained by GPC. The details of the measurement method and measuring equipment are as follows. Apparatus: Waters GPC (ALC / GPC, 150C) Detector: FOXBORO MIRAN, 1A, IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AT-806MS (3 columns) Mobile phase solvent: o-dichlorobenzene (ODCB) ·Measurement temperature: 140℃ ·Flow rate: 1.0mL / min ·Injection volume: 0.2mL The measurement sample is prepared as follows: A 1 mg / mL solution is prepared using the sample and ODCB (containing 0.5 mg / mL dibutylhydroxytoluene (BHT)), and the sample is dissolved at 140° C. for about 1 hour to prepare the measurement sample. The baseline and intervals of the obtained chromatogram are defined as shown in Figure 1. The retention volume obtained by GPC measurement is converted to molecular weight using a calibration curve prepared in advance using standard polystyrenes, all of which are the following brands manufactured by Tosoh Corporation: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000. Each standard was dissolved in ODCB (containing 0.5 mg / mL BHT) to a concentration of 0.5 mg / mL, and 0.2 mL of the solution was injected to create a calibration curve. The calibration curve was calculated using a cubic equation obtained by approximating the curve using the least squares method. Viscosity formula used for conversion to molecular weight: [η] = K × M α The following numerical values ​​are used: PS:K=1.38×10 -4 , α=0.7 PP:K=1.03×10 -4 , α=0.78

[0020] The average molecular weight, molecular weight distribution (Mz, Mw, Mn, Mw / Mn, Mz / Mw) and balance thereof of the branched polypropylene resin (X) measured by GPC can be adjusted by polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc.

[0021] Characteristics (X-2-2): The branched polypropylene resin (X) used in the present invention preferably has an integral molecular weight distribution curve obtained by GPC, in which the ratio (W2 million / W1 million) of the proportion of components having a molecular weight of 2 million or more (W2 million) to the proportion of components having a molecular weight of 1 million or more (W1 million) satisfies the following formula (2): (W2 million / W1 million)<-0.05×log(MFR)+0.34 Formula (2) W2 million / W1 million is the ratio of the amount of components with even higher molecular weights to the amount of components in the high molecular weight region. In the above formula (2), W2 million / W1 million is considered to be a function negatively correlated with an increase in MFR, and the relationship between W2 million / W1 million and MFR was approximately determined based on the data of the branched polypropylene resin (X) used in the present invention and the reference branched polypropylene resin (CX) of the prior art having the same level of fluidity as in the examples. The relationship between W2 million / W1 million and MFR was approximately determined so as to distinguish the branched polypropylene resin (X) that improves the high-speed stretching property during molding from the reference branched polypropylene resin (CX) that is inferior in this effect (see FIG. 2). Satisfying the formula (2) means that W2 million / W1 million is less than a specific value in terms of MFR. In other words, it means that the amount of components with a molecular weight of 2 million or more, which is higher than the amount of components with a molecular weight of 1 million or more, is relatively small. When W2 million / W1 million is in the above range in terms of MFR, it is considered that the components having long relaxation times are prevented from becoming too numerous, and high-speed stretching properties are maintained. Therefore, it is preferable that the branched polypropylene resin (X) used in the present invention satisfies the above formula (2).

[0022] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00% by mass or more and 9.50% by mass or less. It is believed that the melt tension of the branched polypropylene resin (X) used in the present invention increases due to the presence of components in the high molecular weight range. Therefore, in the present invention, attention is focused on components having a molecular weight of 1 million or more, and the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00 mass% or more, or may be 2.00 mass% or more. On the other hand, it is believed that the presence of an appropriate amount of components in the high molecular weight range maintains an appropriate amount of components with long relaxation times, and also maintains high-speed stretching properties. Therefore, W1 million may be 9.50 mass% or less, 8.00 mass% or less, 6.00 mass% or less, or 5.00 mass% or less.

[0023] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass % or less. As in the above, it is believed that the presence of an appropriate amount of components in the very high molecular weight range maintains the components with extremely long relaxation times appropriately, and also maintains high-speed stretching properties. Therefore, in the present invention, attention is focused on components with a molecular weight of 2 million or more, and the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass% or less, 1.00 mass% or less, or 0.70 mass% or less. The branched polypropylene resin (X) used in the present invention may have a W2 million of 0.05 mass% or more.

[0024] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.25 or less, 0.20 or less, or 0.17 or less. As in the above, when W2 million / W1 million is in the above range, it is considered that the components with long relaxation times are prevented from becoming too numerous, and high-speed stretching properties are maintained. The branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.02 or more, 0.03 or more, or 0.05 or more.

[0025] In the present invention, W1 million and W2 million are defined as the value obtained by subtracting from 1 the integral value up to a molecular weight (M) of 1 million (Log(M)=6.0) and up to a molecular weight (M) of 2 million (Log(M)=6.3) in an integrated molecular weight distribution curve (total amount normalized to 1) obtained by GPC, and multiplying the result by 100. An example of an integrated molecular weight distribution curve is shown in FIG. In the present invention, W1 million and W2 million of the branched polypropylene resin (X) can be adjusted by polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc., as described in the characteristic (X-2).

[0026] Characteristics (X-3): The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. The branching index g' is the intrinsic viscosity [η] of a polymer with a long chain branching structure. br Intrinsic viscosity [η] of a linear polymer with the same molecular weight lin Ratio to ([η] br / [η] lin ) When a polymer molecule has long chain branches, it has a smaller radius of gyration and a smaller intrinsic viscosity than a linear polymer molecule of the same molecular weight, so g' is smaller than 1.0. Also, even if the amount of branching is the same, if the branch length is long, it has a smaller radius of gyration and a smaller intrinsic viscosity than a linear polymer molecule of the same molecular weight, so g' is smaller than 1.0. Linear polymers, by definition, have a g' of 1.0. The definition of g' is described in "Developments in Polymer Characterization-4" (JV Dawkins ed. Applied Science Publishers, 1984), and is a known indicator for those skilled in the art. g' was determined by using 3D-GPC. abs can be obtained as a function of In this specification, 3D-GPC refers to a GPC apparatus to which three detectors are connected. The three detectors are a differential refractometer (RI), a viscosity detector (Viscometer) and a multi-angle laser light scattering detector (MALLS).

[0027] The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M abs Weight average molecular weight (Mw abs ) may be less than 1 million, and Mw abs From M abs It is considered that a branched structure in the high molecular weight region of 1,000,000 is preferable in terms of having a high melt tension. Therefore, the branched polypropylene resin (X) used in the present invention has a g' (1 million) of 0.75 or less, preferably 0.74 or less, and more preferably 0.72 or less. abs If the branched structure is appropriately present in the high molecular weight region of g'(1 million) and the branched chain length of the introduced branched structure is appropriate, it is considered that the components with extremely long relaxation times are prevented from becoming too numerous, and high-speed stretching properties can be maintained. Therefore, g'(1 million) is 0.60 or more, preferably 0.62 or more, and more preferably 0.65 or more. In this way, the branched polypropylene resin (X) used in the present invention has M abs It is believed that the amount of components with branched structures in the molecular weight region of 100,000,000 is appropriately large within a specific range, which increases the melt strength and increases the strain hardening index (SHI) and melt tension (MT) in the measurement of extensional viscosity as nonlinear viscoelastic properties. Even if the number of branches is large as a whole polymer, the amount of M corresponding to the high molecular weight component is abs If the amount of components having branches in the M = 1 million portion is small, the SHI does not become large. abs = 1 million, and furthermore, the branch chain length of the introduced branched structure is not too long, which is thought to be able to suppress deterioration of high-speed stretching properties.

[0028] Characteristics (X-3-2): It is believed that the branched polypropylene resin (X) used in the present invention can maintain high-speed stretching properties due to the presence of a suitable amount of components with long relaxation times, similar to the above property (3). Therefore, in the molecular weight distribution curve obtained by 3D-GPC, Mw abs Branching index g'(Mw abs ) may be 0.70 to 0.90. g'(Mw abs The lower limit of may be 0.73 or more, or 0.75 or more, and the upper limit may be 0.87 or less, or 0.86 or less.

[0029] Characteristics (X-3-3): The branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs ) and g' (1 million) may satisfy the following formula (3): 0.10≦g'(Mw abs )-g'(1 million) Formula (3) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs It is believed that the large difference between g(1) and g'(1 million) results in a larger number of components with longer relaxation times, which in turn increases the melt strength. Furthermore, the branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs ) and g' (1 million) may satisfy the following formula (3-2). g'(Mw abs )-g'(1 million)≦0.20 Formula (3-2) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs It is considered preferable that the difference between g(1,000,000) and g'(1,000,000) is not too large, since this prevents the proportion of components having extremely long relaxation times from becoming too high, thereby improving the high-speed stretching properties. In addition, the branched polypropylene polymer of the present invention is considered to be preferable since the branching distribution is within the above range, making it possible to maintain a balance between the melt strength and the high-speed stretching properties as a whole.

[0030] M abs The method for measuring the molecular weight distribution and the branching index at each molecular weight is as follows: The detectors are connected in the order of MALLS, RI, and Viscometer. Equipment: Alliance GPCV2000 (GPC equipped with RI and Viscometer) manufactured by Waters, DAWN-E (MALLS) manufactured by Technology Column: Tosoh GMHHR-H(S)HT (2 columns) Mobile phase solvent: 1,2,4-trichlorobenzene (with antioxidant Irganox 1076 (BASF Japan) added at a concentration of 0.5 mg / mL) ·Measurement temperature: 140℃ ·Flow rate: 1mL / min Sample concentration: 1mg / mL ·Injection volume: 0.2175mL M obtained from MALLS abs The root mean square radius of gyration (Rg) and the intrinsic viscosity ([η]) obtained from the Viscometer are calculated using the data processing software ASTRA (version 4.73.04) attached to MALLS, with reference to the following literature. References: 1.Developments in Polymer Characterization, vol.4. Essex: Applied Science; 1984. Chapter1. 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000) g' is the intrinsic viscosity ([η] br ) and the intrinsic viscosity ([η] obtained by separately measuring a linear polymer lin ) and the ratio ([η] br / [η] lin ) is calculated as follows. Here, a commercially available homopolypropylene (Novatec PP (registered trademark) manufactured by Japan Polypropylene Corporation, grade name: FY6) was used as the linear polymer, and [η] lin [η] of linear polymer lin The logarithm of [η] has a linear relationship with the logarithm of the molecular weight, as known from the Mark-Houwink-Sakurada equation. lin can be obtained by extrapolating to the low molecular weight side or the high molecular weight side as appropriate.

[0031] In the present invention, the g' (million) and g' (Mw abs ), g'(Mw abs As explained in the characteristic (X-2), )-g' (million) can be adjusted by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc. Among them, it is preferable to adjust by selecting the catalyst type, and although there is no particular limitation, it is appropriate to adjust by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.

[0032] Among them, g'(Mw abs It is preferable that the condition where (g)-g' (million) satisfies the formula (3) or the formula (3-2) is adjusted by selecting a catalyst from a plurality of catalyst species or a plurality of metallocene compounds. For example, when a catalyst consisting of a single catalyst type or a single metallocene compound (hereinafter, sometimes collectively referred to as a single catalyst) is used instead of a catalyst consisting of multiple catalyst types or multiple metallocene compounds, it is considered that formula (3) or formula (3-2) is not satisfied. This is because, with a single catalyst, the molecular weight distribution of the macromonomer produced is narrow, and macromonomers with significantly different molecular weights are not supplied, so the value of formula (3) is expected to be small, or the value of formula (3-2) to be large. To explain this using Reference Example 2 as an example (see Table 2), g'(Mw abs ) is large, so Mw abs Since there are no components with short branched chains, it is estimated that the molecular weight of the macromonomer produced by this catalyst is high. On the other hand, since g' (1 million) is small, it is assumed that the molecular weight of the macromonomer produced by this catalyst is high. abs It is estimated that there are branched components due to macromonomers with large molecular weights in the range of g'(Mw = 1 million). Thus, in a single catalyst that produces macromonomers with a narrow molecular weight distribution, for example, abs )-g' (million) becomes large and equation (3-2) is not satisfied.

[0033] Characteristics (X-4): From the viewpoint of improving the quality of a film produced by an inflation molding method, the branched polypropylene resin (X) used in the present invention has a flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity that satisfy the following formula (1): Ea≧-12.5×log(MFR)+66 Equation (1)

[0034] In general, the viscosity of an object decreases as its temperature increases, and the logarithm of viscosity, lnη, is proportional to the reciprocal of absolute temperature, 1 / T, and it has long been known empirically that it can be expressed by the following formula (Chemical Dictionary, 2nd Edition, "Andrade's Viscosity Formula").

[0035]

number

[0036] This energy term Ea corresponds to the activation energy when the reaction rate in an Arrhenius chemical reaction is considered to be a flow, and is called the flow activation energy. "High Ea" means "the energy required to make the polymer flow is large." In the case of branched polypropylene resin (X), it is considered that if the amount of branches is large or the branch length is long, the molecular chains become more entangled, and the energy required to make the molecular chains flow is large. In other words, Ea mainly depends on the amount and length of long chain branches in the polymer. In the branched polypropylene resin (X) used in the present invention, the relationship between Ea and MFR was specified, focusing on Ea as an index for obtaining appropriate branching properties to improve the quality and processability of the film produced by the inflation molding method.

[0037] From the viewpoint of improving the quality and processability of the film, the branched polypropylene resin (X) used in the present invention may have an Ea of 55.0 kJ / mol or more, or 58.0 kJ / mol or more, or may have an Ea of 70.0 kJ / mol or less.

[0038] Satisfying the formula (1) means that the branched polypropylene resin (X) used in the present invention has an Ea obtained by measuring the dynamic viscoelasticity of at least a specific value in proportion to the MFR. The branched polypropylene resin (X) used in the present invention has an Ea value corresponding to the MFR different from that of conventional propylene polymers, that is, satisfies the formula (1). If Ea is too small in relation to the MFR, the branching characteristics including the branch amount, branch length, and branching distribution become inappropriate, and the high-speed stretching characteristics during molding become poor. Therefore, the branched polypropylene resin (X) used in the present invention satisfies the above formula (1). More preferably, it may satisfy the following formula (1-2). Ea≧-12.5×log(MFR)+72 Equation (1-2)

[0039] Generally, when the fluidity of a molten resin is increased, Ea decreases, so it is desirable to have a branched polypropylene resin that has both the necessary fluidity and Ea, which is an index of branching properties suitable for improving high-speed stretching properties during molding. A branched polypropylene resin (X) that has excellent fluidity and satisfies formula (1) can be said to have a high balance between the fluidity and branching properties of a molten resin. In addition, the above formula considers Ea to be a function that has a negative correlation with an increase in MFR, and the relationship between Ea and MFR was approximately determined based on the data of the branched polypropylene resin (X) used in the present invention and the reference branched polypropylene resin (CX) of the prior art that has the same level of fluidity as the examples. The relationship between Ea and MFR was approximately determined so as to distinguish between a branched polypropylene resin (X) that improves high-speed stretching properties during molding and a reference branched polypropylene resin (CX) that is inferior in this effect (see FIG. 4).

[0040] The branched polypropylene resin (X) used in the present invention is presumed to have a high flow activation energy (Ea) corresponding to the MFR, since the branching characteristics including the branch amount, branch length and branch distribution are suitable for improving the high-speed stretching properties during molding. It is believed that if Ea is high relative to MFR, the extrusion load during molding can be reduced more compared to branched polypropylene resins with the same MFR. The branched polypropylene resin (X) used in the present invention satisfies the above formula (1), and therefore can improve the high-speed stretching properties while reducing the extrusion load during molding.

[0041] The upper limit of Ea in relation to the MFR is not particularly limited, but may satisfy the following formula (1-3) or may satisfy the following formula (1-4). Ea≦-12.5×log(MFR)+82 Equation (1-3) Ea≦-12.5×log(MFR)+77 Equation (1-4)

[0042] Ea is a value calculated from the shift factor (aT) when creating a master curve based on the temperature-time superposition principle in the measurement of melt viscoelasticity by the Arrhenius equation. In the present invention, the master curve is a curve showing the angular frequency (unit: rad / sec) dependency of the melt complex viscosity (unit: Pa·sec) at 200°C. Ea can be determined by the following method. First, for three temperatures of 180°C, 200°C, and 220°C, the melt complex viscosity-angular frequency curve of the branched polypropylene resin (X) at each temperature (T, unit: °C) is obtained. Based on the temperature-time superposition principle, each melt complex viscosity-angular frequency curve is superimposed on the melt complex viscosity-angular frequency curve at 200°C to obtain each shift factor (aT). From each temperature (T) and aT at each temperature (T), a linear approximation equation (the following equation (4)) of [ln(aT)] and [1 / (T+273.16)] is calculated by the least squares method. Next, Ea is obtained from the slope m of the linear equation and the following equation (5). ln(aT)=m(1 / (T+273.16))+n Equation (4) Ea = |0.008314 × m| Equation (5) aT: Shift factor Ea: Flow activation energy (unit: kJ / mol) T: Temperature (unit: ℃) The above calculations may be carried out using commercially available software, such as Trios manufactured by TA Instruments. Note that aT is the amount of movement in the x-axis direction when the log-log curve of melt complex viscosity vs. angular frequency at each temperature (T) is moved in the x-axis (angular frequency) and y-axis (melt complex viscosity) directions and superimposed on the melt complex viscosity vs. angular frequency curve at 200°C. The melt complex viscosity-angular frequency curve is measured using a viscoelasticity measuring device (for example, ARES-G2 manufactured by TA Instruments) under a nitrogen atmosphere under the following conditions. The propylene polymer is compression molded at 180°C for 5 minutes while being careful not to trap air bubbles, to obtain a disk-shaped measurement sample having a thickness of 2.0 mm and a diameter of 25 mm. Measurements of the sample are performed at three temperatures, 180°C, 200°C, and 220°C, using parallel disks having a diameter of 25 mm that are kept at each temperature, after which the measurement sample having a thickness of 2.0 mm is compressed to a thickness of 1.5 mm. Geometry: Parallel plate Plate diameter: 25mm Plate spacing: 2mm Strain: 5% Angular frequency: 0.01~100rad / sec

[0043] In the present invention, the Ea and MFR of the branched polypropylene resin (X) can satisfy the above formula (1) by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc., as explained in the characteristic (X-2). Among these, it is preferable to adjust by selecting the catalyst type, and although there is no particular restriction, it is appropriate to adjust by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.

[0044] Characteristics (X-5): The branched polypropylene resin (X) used in the present invention is 13 The meso triad fraction (mm) measured by C-NMR is preferably 95.0% or more and less than 99.0%. Characteristics (X-5-2): In addition, the branched polypropylene resin (X) used in the present invention preferably has a heterogeneous bond ([2,1 bond]) content of 0 mol % to 0.30 mol % and a heterogeneous bond ([1,3 bond]) content of 0 mol % to 0.25 mol %.

[0045] The crystallinity of the branched polypropylene resin (X) is affected by the stereoregularity indicated by the mesotriad fraction (mm) and mesopentad fraction (mmmm) and the regioregularity indicated by [2,1 bond] and [1,3 bond]. In other words, crystallization proceeds by folding back the lamellae from the irregularity-defective parts (sterically irregular bonds and heterogeneous bonds). When the branched polypropylene resin (X) used in the present invention has a stereoregularity and a regioregularity within the above ranges, it is believed that the fluidity of the resin during gradual cooling and solidification during molding and the melt tension during solidification are improved due to a crystallization process caused by shear or elongation deformation.

[0046] In order to improve the melt tension of the branched polypropylene resin (X) when solidified, the mm of the branched polypropylene resin (X) used in the present invention is preferably 95.0% or more, more preferably 96.0% or more, and even more preferably 97.0% or more. On the other hand, if mm is too high, the rigidity and Young's modulus become high, and the film may become too stiff. Therefore, mm of the branched polypropylene resin (X) used in the present invention is preferably less than 99.0%, more preferably 98.5% or less, and more preferably 98.2% or less.

[0047] Similarly, from the viewpoint of improving the melt tension during solidification, the amount of [2,1 bond] in the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.30 mol%, more preferably 0 mol% to 0.25 mol%, even more preferably 0 mol% to 0.20 mol%, even more preferably 0.030 mol% to 0.25 mol%, and particularly preferably 0.05 mol% to 0.20 mol%. The upper limit of the amount of [2,1 bond] may be 0.15 mol% or less. In addition, in combination with the amount of [2,1 bond], the amount of [1,3 bond] in the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.25 mol%, more preferably 0 mol% to 0.20 mol%, even more preferably 0 mol% to 0.15 mol%, even more preferably 0.05 mol% to 0.20 mol%, and particularly preferably 0.10 mol% to 0.15 mol%.

[0048] 13 The methods for measuring and calculating the amounts of mm, [2,1 bond] and [1,3 bond] measured by C-NMR are as follows. A 200 mg sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene (C6D5Br) = 2 / 1 (volume ratio) and hexamethyldisiloxane, a chemical shift standard substance, and dissolved uniformly in a block heater at 150 °C to prepare a measurement sample. ( 1 H-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 4.5° Pulse Interval: 2 seconds Number of times of accumulation: 1024 times Chemical shift: The chemical shift is set to 0.09 ppm for the proton signal of hexamethyldisiloxane, and the chemical shifts of the signals due to other protons are based on this. ( 13 C-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 45° Pulse Interval: 17.2 seconds Number of times: 3072 Decoupling conditions: Broadband decoupling method Chemical shift: Chemical shifts of hexamethyldisiloxane 13 The C signal was set at 1.98 ppm, and the other 13 The chemical shifts of the C signals are based on this.

[0049] The meso triad fraction (mm) of three propylene units is 13 Measured by C-NMR 13 The integrated intensity of the C signal can be calculated by substituting it into the following equation (6). mm(%)=I mm ×100 / (I mm +3×I mrrm ) Formula (6) Here I mm is assigned to the mm bonding mode of three propylene units. 13 The integrated intensity of the C signal is shown in Fig. 1. The integrated intensity of the signal with a chemical shift in the range of 23.6 to 21.1 ppm (hereinafter referred to as "I 23.6~21.1 " is used as the calculation. mrrm is assigned to the 5-propylene unit sequence as the mrrm bond mode. 13 C represents the integrated intensity of the signal, I 19.9~19.7 The value is shown below. Spectral assignment can be done with reference to Polymer Jounral, vol. 16, p. 717 (1984), Asakura Publishing, Macromolecules, vol. 8, p. 687 (1975), and Polymer, vol. 30, p. 1350 (1989). The chemical shift range shifts slightly depending on the molecular weight of the polymer, but it is easy to distinguish the regions.

[0050] The amount of [2,1 bond] and [1,3 bond] is 13 Measured by C-NMR 13It is calculated using the integrated intensity of the C signal according to the following formula. [2,1 bond] amount (mol%)=I 2,1-P ×100 / (I 1,2-P +I 2,1-P +I 1,3-P ) [1,3 bond] amount (mol%)=I 1,3-P ×100 / (I 1,2-P +I 2,1-P +I 1,3-P ) Here, I 1,2-P , I 2,1-P , I 1,3-P are assigned to the bonding modes of [1,2 bond], [2,1 bond], and [1,3 bond] in the propylene units, respectively. 13 It represents the integrated intensity of the C signal and is calculated as follows: I 1,2-P =I 48.80~44.50 I 2,1-P =(I 34.68~34.63 +I 35.47~35.40 +I 35.94~35.70 ) / 2 I 1,3-P =I 37.50~37.20 / 2

[0051] The above properties (X-5) and (X-5-2) can be satisfied by adjusting polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration, and amount of hydrogen.

[0052] Characteristics (X-6): The branched polypropylene resin (X) used in the present invention has the following properties: 13 The number of long chain branches (LCB number) measured by C-NMR is preferably 0.1 to 0.5 per 1000 monomers, and more preferably 0.2 to 0.5 per 1000 monomers.

[0053] The number of LCBs is 13The number per 1000 propylene monomers is calculated using the following formula using the signal integral intensities of the branch point carbon (methine carbon) at 31.72 to 31.66 ppm and three methylene carbons bonded to the branch point carbons (methine carbon) at 44.09 to 44.03 ppm, 44.78 to 44.72 ppm, and 44.90 to 44.84 ppm when the intensity of the methylene carbons in the propylene main chain at 49.00 to 44.33 ppm is normalized to 1000 by C-NMR. Number of LCBs = [(I 44.09~44.03 +I 44.78~44.72 +I 44.90~44.84 +I 31.72~31.66 ) / 4] / I 49.00~44.33 When calculating the LCB number 13 The C-NMR measurement was performed under the same conditions as in the above (X-5), except that the measurement conditions were changed as follows: 13 This can be done in the same manner as C-NMR measurement. Pulse Interval: 4.2 seconds -Number of times: 20,000

[0054] The characteristic (X-6) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and amount of hydrogen, in the same manner as described for the characteristic (X-4).

[0055] Characteristics (X-7): The branched polypropylene resin (X) used in the present invention has a strain hardening index (SHI@1s -1 ) is preferably 0.70 to 2.50. Here, SHI@1s -1 is the extensional viscosity (η E In the measurement of the Hencky strain (ε) between 1 and 3, the horizontal axis is the logarithm of the Hencky strain (log(ε)) and the vertical axis is the logarithm of the extensional viscosity (log(η E ) is the slope when plotting In order to increase the melt tension to improve moldability and to improve high-speed stretching properties, the SHI@1s of the branched polypropylene resin (X) used in the present invention is -1is preferably from 0.70 to 2.50, more preferably from 0.80 to 2.00, and further preferably from 1.00 to 1.80. Branched polypropylene resin (X) is SHI@1s -1 When SHI@1s is relatively large, the extensional viscosity increases due to the presence of components in the polymer that do not relax at high strain rates. Therefore, linear polymers that do not have strain hardening at high strain rates and SHI@1s -1 Compared to polymers with a smaller elongational viscosity, the melt tension is increased due to the higher elongational viscosity, which is thought to improve moldability in sheet molding, blow molding, thermoforming, and foam molding. From this viewpoint, the branched polypropylene resin (X) used in the present invention is SHI@1s -1 is preferably 0.70 or more. Branched polypropylene resin (X) is SHI@1s -1 When SHI@1s is appropriately large, the amount of components that do not relax or components that relax for a long time is appropriately maintained, and strain hardening occurs due to an appropriate molecular weight distribution. From the viewpoint of suppressing periodic bubble vibration during high-speed inflation molding and maintaining high-speed stretching properties, the branched polypropylene resin (X) used in the present invention has a SHI@1s -1 It is preferable that the ratio is 2.50 or less.

[0056] The strain hardening index (SHI) can be determined by measuring the uniaxial extensional viscosity as described in Polymer, Vol. 42, p. 8663 (2001). In the present invention, SHI@1s -1 is measured by the following method. Equipment: TA Instruments ARES-G2 Fixture: TA Instruments Extensional Viscosity Fixture ·Measurement temperature: 180℃ ·Strain rate: 1.0 / sec - Preparation of test specimen: A sheet of 18 mm x 10 mm and 0.7 mm thick was prepared by press molding.

[0057] To calculate the SHI, the above measurement method is used to obtain data on the time change in elongational viscosity at a predetermined constant strain rate, and the measurement data is plotted as log(ε) on the horizontal axis and log(η) on the vertical axis. E ) is plotted on a graph. Then, the slope of the extensional viscosity in the Hencky strain range between 1 and 3 is identified from the graph, and this slope is taken as the SHI at the strain rate under the measurement conditions.

[0058] The characteristic (X-7) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-4).

[0059] Characteristics (X-8): The branched polypropylene resin (X) used in the present invention preferably has a multi-branching index (MBI) of 0.20 or more in order to provide excellent high-speed stretching properties during molding, and preferably has a MBI of 1.00 or less in order to obtain stable melt tension by suppressing the strain rate dependency of strain hardening. The lower limit of the MBI is more preferably 0.26 or more, and the upper limit is more preferably 0.80 or less, and further preferably 0.60 or less. Here, MBI is the slope of a plot of the SHI of a polymer at strain rates of 0.1 / sec to 10 / sec, with the logarithm of the strain rate (log(dε / dt)) on the horizontal axis and the SHI at strain rates of 0.1 / sec to 10 / sec on the vertical axis. The SHI of a polymer changes with strain rate. The MBI indicates the dependence of the SHI on the strain rate. A larger MBI value means that the SHI increases more with increasing strain rate. To obtain the MBI, SHI is measured at multiple strain rates in the range of 0.1 / sec to 10 / sec, and the SHI at each strain rate is plotted on a graph with log(dε / dt) on the horizontal axis and SHI on the vertical axis. The slope of the approximation line of the plot in the range of strain rates from 0.1 / sec to 10 / sec is defined as the MBI. -1 , SHI@1.0s -1 , SHI@10.0s -1The slope of the line obtained by approximating the plot of the three points using the least squares method was determined as the MBI.

[0060] The characteristic (X-8) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-4).

[0061] Characteristics (X-9): The branched polypropylene resin (X) used in the present invention may have a melt tension at 230°C (MT230) of 0.3 g to 15 g, or 0.5 g to 15 g, in order to obtain a propylene polymer having excellent high-speed stretching properties while maintaining a melt tension necessary for molding. In the present invention, MT230 is defined as the tension detected at a pulley when a resin is extruded in a string-like form and wound around a roller under the following conditions using a melt tension tester (for example, Capilograph 1B manufactured by Toyo Seiki Seisakusho). ·Resin temperature: 230℃ Capillary: diameter 2.0mm, length 40mm Cylinder diameter: 9.55mm Cylinder extrusion speed: 20mm / min · Winding speed: 4.0m / min If the resin breaks at a winding speed of 4.0 m / min, the melt tension is deemed "unable to evaluate."

[0062] Characteristics (X-10): The branched polypropylene resin (X) used in the present invention may have a maximum draw speed (MaxDraw) m / min at 230° C. and an MFR that satisfy the relationship represented by the following formula (7). (MaxDraw)>200×log(MFR)-38 Equation (7) Here, MaxDraw is the melt tension measurement, in which the resin is extruded into a string shape and wound around a roller, and the winding speed is increased from 4.0 m / min to an acceleration of 18.1 mm / sec. 2 This is the winding speed just before the string-shaped resin breaks when the winding speed is gradually increased. If the resin breaks at a winding speed of 4.0 m / min, it is deemed "evaluation not possible." The high-speed stretching property can be evaluated using MaxDraw as an index, and the larger MaxDraw is, the better the high-speed stretching property is. In the present invention, MaxDraw was measured under the following conditions. Equipment: INSTRON capillary rheometer CEAST SR50 Capillary: diameter 2.0mm, length 40mm Barrel diameter: 15mm Barrel length: 290mm Cylinder extrusion speed: 20mm / min ·Resin temperature: 230℃

[0063] Generally, increasing the fluidity leads to excellent high-speed stretching properties, but the melt tension decreases. Increasing the fluidity to improve high-speed stretching properties leads to the problem that the melt tension becomes insufficient. Therefore, a propylene-based polymer that has both the melt tension required for molding and excellent high-speed stretching properties is desired. The relationship between MaxDraw and MFR defined by the above formula (7) can be used as an index of high-speed stretching properties commensurate with fluidity. Satisfying the above formula (7) indicates that the branched polypropylene-based resin (X) used in the present invention has excellent high-speed stretching properties commensurate with fluidity, compared to conventional propylene-based polymers. That is, in order to distinguish the branched polypropylene resin (X) used in the present invention from the conventional ones, the high-speed stretching property (MaxDraw as an index) is considered to be a function positively correlated with the increase in fluidity (MFR as an index), the parameters of the function are set, and the MaxDraw of the branched polypropylene resin (X) used in the present invention is shown to be larger in proportion to the MFR than the MaxDraw of the conventional propylene polymer defined by the function. Specifically, based on the data of the branched polypropylene resin (X) used in the present invention and the reference branched polypropylene resin (CX) of the conventional technology having the same level of fluidity as the examples, the relational equation between MaxDraw and MFR was approximately determined. Assuming the values ​​of MaxDraw and MFR that distinguish the branched polypropylene resin (X) with improved high-speed stretching property during molding from the reference branched polypropylene resin (CX) with inferior effect, the parameters of the relational equation that holds between the MaxDraw and MFR were determined by the least squares method (see FIG. 5).

[0064] 1-2. Manufacturing method of branched polypropylene resin (X) The method for producing the branched polypropylene resin (X) used in the present invention is not particularly limited as long as it is a method that can produce a branched polypropylene resin (X) having the above-mentioned properties that are characteristic of the present invention. However, a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is suitable. The present inventors speculate that the mechanism of the macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is as follows. When polymerization is performed using a catalyst containing a metallocene compound (referred to as compound 1) that forms a catalyst that mainly produces a macromonomer and a metallocene compound (referred to as compound 2) that forms a catalyst that mainly copolymerizes a macromonomer and a propylene monomer to produce a polymer having a branched chain, the following polymerization behavior is observed. By using a propylene polymerization catalyst containing compound 1 and compound 2, it is possible to obtain a polymer having a molecular weight range that includes a molecular weight distribution that is a combination of the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 1 (catalyst 1) and the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 2 (catalyst 2). In the process of forming the branched structure, when the polymer produced from catalyst 1 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 1), and further, a copolymer of propylene and macromonomer 1 is produced from catalyst 1, and a copolymer of propylene and macromonomer 1 is produced from catalyst 2. When the polymer produced from catalyst 2 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 2), and further, a copolymer of propylene and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene and macromonomer 2 is produced from catalyst 2. Furthermore, when the polymer produced from catalyst 1 is macromonomer 1 and the polymer produced from catalyst 2 is macromonomer 2, furthermore, a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 2. In this way, depending on the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 1 of the polymer produced from catalyst 1, the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 2 of the polymer produced from catalyst 2, the quantitative ratio and steric positional relationship between catalyst 1 and catalyst 2, the average molecular weight, high molecular weight, and very high molecular weight of the branched polypropylene resin (X) as the final product, as well as the amount and branch distribution, change. That is, Mn, Mw, Mz, W 1 million, W 2 million, g' (1 million), g' (Mw abs ), [g'(Mw abs )-g'(million)], Ea, SHI, MBI, MT, etc. are expected to change.

[0065] A preferred method for producing the branched polypropylene resin (X) used in the present invention is not limited to the above mechanism, but may be, for example, the following. In the method for producing the branched polypropylene resin (X) used in the present invention, from the viewpoint of easily satisfying the above-mentioned characteristics, it is preferable to carry out polymerization using a polymerization catalyst in which two catalyst components, component [A-1] and component [A-2], which generate a macromonomer, are used and the types, amounts and amount ratio of component [A-1] and component [A-2] are selected and combined so that the following conditions are satisfied: a) The molecular weight of the polymer produced from component [A-2] is higher than that of the polymer produced from component [A-1], b) The proportion of terminal vinyl in the polymer produced from component [A-1] is greater than the proportion of terminal vinyl in the polymer produced from component [A-2]; c) Component [A-2] has better copolymerizability with the macromonomer than component [A-1].

[0066] The propylene polymerization catalyst for producing the branched polypropylene resin (X) used in the present invention preferably contains the following components [A-1], [A-2], [B] and [C]. Component [A-1]: a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerized at 70°C; Component [A-2]: a metallocene compound which, when propylene homopolymerized at 70°C, gives a propylene homopolymer a-2 having a larger Mn than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and less than 0.5. Component [B]: a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair Component [C]: Organoaluminum compound

[0067] Component [A-1] is a metallocene compound that gives a propylene homopolymer a-1 with an Rv of 0.5 or more when propylene homopolymerization is carried out at 70 °C. Component [A-1] is preferably a metallocene compound with an Rv of 0.65 or more, more preferably 0.75 or more, and ideally 1.0 (one end of all molecular chains has a vinyl structure). By using a metallocene compound that forms a polymerization catalyst for producing a propylene homopolymer with a higher Rv, a more efficient macromonomer synthesis step can be carried out. Here, the terminal vinyl ratio (Rv) and the terminal vinylidene ratio (Rvd) are defined by the following formulas. Rv = [Vi] / {(total number of terminals - number of LCBs) ÷ 2} Rvd = [Vd] / {(total number of terminals - number of LCBs) ÷ 2} (However, [Vi] and [Vd] are 1 the number of terminal vinyl groups and the number of terminal vinylidene groups per 1000 monomers calculated by 1H-NMR. The total number of terminals is 1 calculated by 1H-NMR and 13 the total number of terminals per 1000 monomers calculated by 13C-NMR. The number of LCBs is 13 the number of LCBs per 1000 monomers calculated by 13C-NMR.)

[0068] [Relationship between reaction mechanism and terminal structure], [Evaluation method of terminal vinyl ratio (Rv) and terminal vinylidene ratio (Rvd)], <Calculation method of the number of saturated terminals>, <Calculation method of the number of unsaturated terminals>, <Calculation method of the number of LCBs>, <Calculation method of the total number of terminals>, and <Calculation method of terminal vinyl ratio (Rv) · terminal vinylidene ratio (Rvd)> can refer to the descriptions in paragraphs 0073 to 0080 of International Publication No. 2022 / 209773. In addition, the polymerization conditions of propylene when determining Rv and Rvd of the catalyst component are as follows. After replacing the inside of the 20L autoclave tank with propylene, 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) is added, 0.51NL of hydrogen is introduced, and 5000g of liquid propylene is introduced. Then, 300mg of a catalyst containing component [A-1] is pumped into the tank (excluding the prepolymerized polymer) to start polymerization, and polymerization is carried out at 70℃ for 1 hour. Finally, the unreacted propylene is quickly purged, and the polymerization is stopped to obtain a propylene polymer.

[0069] Examples of the component [A-1] include bisindenyl complexes having a bulky heterocyclic group at the 2-position of the indenyl group and an aryl group or a heterocyclic group containing a nitrogen, oxygen or sulfur atom that may be substituted at the 4-position. Specific examples of the component [A-1] can be found in paragraphs 0081 to 0088 of WO 2022 / 209773.

[0070] The component [A-2] is a metallocene compound which, when propylene homopolymerized at 70°C, gives a propylene homopolymer a-2 having a larger Mn and an Rv of 0.1 or more and smaller than 0.5 than those of the propylene homopolymer a-1.

[0071] The component [A-2] is a metallocene compound that forms a polymerization catalyst for copolymerizing a propylene monomer and a propylene macromonomer and for producing a propylene macromonomer. Therefore, the component [A-2] is a metallocene compound having an Rv of 0.1 or more, preferably 0.15 or more, and more preferably 0.2 or more. On the other hand, as the component [A-2], a metallocene compound that has a high molecular weight and a low Rv but forms a polymerization catalyst that efficiently copolymerizes a macromonomer is used, thereby making it possible to suppress the generation of high molecular weight branched components with long branches. Therefore, the component [A-2] is a metallocene compound having an Rv of less than 0.5, preferably 0.45 or less, and more preferably 0.3 or less.

[0072] Furthermore, in order to obtain the average molecular weight, molecular weight distribution and branching distribution, which are the characteristics of the branched polypropylene resin (X) used in the present invention, such that Mw, Mz and g' (1 million) have the above-mentioned properties, and preferably W2 million / W1 million satisfies the above-mentioned properties, it is necessary for component [A-2] to produce a polymer having a higher molecular weight than component [A-1]. Therefore, component [A-2] is a metallocene compound that produces a higher molecular weight polymer than component [A-1] when propylene homopolymerization is performed at 70°C with the same amount of hydrogen.

[0073] In order to obtain an average molecular weight, molecular weight distribution and branching distribution such that the branched polypropylene resin (X) used in the present invention satisfies the above-mentioned properties, it is preferable that the component [A-2] has a better copolymerizability of the macromonomer than the component [A-1]. Therefore, it is preferable that component [A-2] is a metallocene compound in which, when propylene is homopolymerized at 70°C, the proportion of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is greater than that of component [A-1].

[0074] By selecting the component [A-2] as described above, it is possible to preferentially cause the reaction in which the macromonomer with a relatively small molecular weight produced in the component [A-1] is copolymerized with the component [A-2]. The evaluation method for Rv and Rvd is the same as that for component [A-1], except that 100 mg of a catalyst containing component [A-2] (excluding the prepolymerized polymer) is used and 1.19 NL of hydrogen is introduced to polymerize. In addition, the Mw characteristics can be evaluated in the same manner as in the evaluation of Rv and Rvd, by performing bulk polymerization at 70°C, measuring the polymers produced from component [A-2] and component [A-1] by GPC, and comparing the Mw values ​​obtained. Furthermore, the copolymerization characteristics of the macromonomer can be evaluated by performing bulk polymerization at 70°C in the same manner as in the evaluation of Rv and Rvd, and comparing the proportion of the number of terminal vinyls produced that have copolymerized into LCBs {LCB number / ([Vi]+LCB number)} obtained by NMR measurement of the polymer produced from component [A-2] and component [A-1].

[0075] As described above, the ratio of macromonomer in the polymer produced from component [A-2] is lower than that in the polymer produced from component [A-1], so the amount of copolymerization of macromonomer 2 is suppressed. On the other hand, since macromonomer copolymerization is better than that of component [A-1], the branch chain length can be adjusted in the introduced branch structure of branched polypropylene resin (X) by efficiently copolymerizing macromonomer 1. By utilizing this branch chain length adjustment, it is possible to obtain a branched polypropylene resin (X) having the average molecular weight, molecular weight distribution and branch distribution, branch structure, and melt properties (Ea, etc.) resulting therefrom, such that Mw, Mz, and g' (1 million), which are the characteristics of the branched polypropylene resin (X) used in the present invention, satisfy the above-mentioned properties.

[0076] The component [A-2] may be, for example, a metallocene compound of formula (I) described in JP-A-2007-528925. In particular, the component [A-2] may be a metallocene compound of formula (IV) described in JP-A-2007-528925.

[0077] Specific examples of the metallocene compound of formula (IV) described in JP-A-2007-528925 are shown below, but the invention is not limited thereto. Dimethylsilylenebis(cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(5-methyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,3,5-trimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(4-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(2,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-di-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride

[0078] Other examples include compounds in which one or both of the dichlorides in the above-listed compounds are replaced with a bromine atom, an iodine atom, a methyl group, a phenyl group, a dimethylamino group, a diethylamino group, etc. In addition, when an asymmetric carbon is generated in these metallocene compounds, one of the stereoisomers or a mixture thereof (including a racemic mixture) is shown unless otherwise specified.

[0079] As a synthesis method for the metallocene complex represented by the general formula [a2], a conventionally known synthesis method can be appropriately selected and used. For example, the synthesis can be performed by referring to JP-T-2007-528925 and JP-A-2021-152155.

[0080] Component [B] is a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair. Component [B] may be used alone or in combination of two or more thereof. Component [B] is preferably a layered silicate. As the component [B], a conventionally known component can be appropriately selected and used. For specific examples of the component [B], reference can be made to paragraphs 0103 to 0111 of International Publication No. WO 2022 / 209773.

[0081] The component [C] used in the present invention is an organoaluminum compound, and a conventionally known one can be appropriately selected and used. For the component [C], reference can be made to paragraph 0112 of International Publication No. WO 2022 / 209773.

[0082] In addition, the preparation of the olefin polymerization catalyst preferably used in the present invention can be appropriately selected and used according to a conventionally known method, for example, by referring to paragraphs 0113 to 0116 of International Publication No. 2022 / 209773.

[0083] In addition, the polymerization method of the branched polypropylene resin (X) used in the present invention includes a method of homopolymerizing propylene or copolymerizing propylene and a comonomer in the presence of a propylene polymerization catalyst containing components [A-1], [A-2], [B] and [C]. As a specific polymerization method, a conventionally known method can be appropriately selected and used, and for example, paragraphs 0117 to 0123 of WO2022 / 209773 can be referred to.

[0084] The branched polypropylene resin (X) used in the present invention may be in the form of powder, particles, etc. Here, the particulate branched polypropylene resin (X) includes granulated products of the branched polypropylene resin (X).

[0085] When additives are mixed with the branched polypropylene resin (X), a Henschel mixer, a V blender, a ribbon blender, a kneader and / or a tumbler blender, etc. can be used. For the production of granules, a kneader such as a single screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer can be used.

[0086] 2. Polypropylene resin (Y) The polypropylene-based resin (Y) used in the present invention may be a homopolymer of propylene, or a copolymer of propylene and one or more comonomers selected from α-olefin comonomers having 2 to 20 carbon atoms other than propylene, such as ethylene, 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene, etc. However, the polypropylene-based resin (Y) used in the present invention has the following characteristic (Y-2) and is different from the branched polypropylene-based resin (X). The polypropylene-based resin (Y) used in the present invention may be a propylene-based polymer comprising propylene, ethylene, and 0 to 11 mol % of an α-olefin having 4 or more carbon atoms. The polypropylene-based resin (Y) used in the present invention is preferably a propylene homopolymer from the viewpoint of increasing the strength of the film.

[0087] 2-1. Characteristics of polypropylene resin (Y) Characteristics (Y-1): The polypropylene resin (Y) used in the present invention has a melt flow rate (MFR) measured at a temperature of 230° C. and a load of 2.16 kg of 0.1 g / 10 min or more and less than 10 g / 10 min from the viewpoints of ease of inflation molding of the polypropylene resin composition and transparency and strength of the film. The MFR (230° C., load 2.16 kgf) of the polypropylene resin (Y) is preferably 0.1 g / 10 min to 8 g / 10 min, more preferably 0.1 g / 10 min to 6 g / 10 min. The MFR of the polypropylene resin (Y) can be adjusted by changing the temperature conditions during propylene polymerization, changing the pressure conditions during propylene polymerization, and / or changing the method of adding a chain transfer agent such as hydrogen during polymerization.

[0088] Characteristics (Y-2): The polypropylene resin (Y) used in the present invention has an absolute molecular weight M in a molecular weight distribution curve obtained by 3D-GPC from the viewpoints of ease of inflation molding of the polypropylene resin composition and film strength. absThe branching index g' (million) is 0.95 or more, and may be 0.97 or more. As mentioned above, the upper limit of g' is 1.00 by definition. A polypropylene resin with a g' (million) of approximately 1 indicates that the molecular shape is linear. g' (million) can be determined in the same manner as characteristic (X-3) above. As explained in the characteristic (X-3), g' (million) can be adjusted by adjusting the polymerization conditions, such as the selection of catalyst species, polymerization temperature, monomer concentration, amount of hydrogen, etc. Among them, it is preferable to adjust g' by selecting the catalyst species.

[0089] Characteristics (Y-3): In the polypropylene resin (Y) used in the present invention, from the viewpoints of processability in high-speed inflation and transparency and strength of the film produced by high-speed inflation, the melting point (Tm) measured by differential scanning calorimetry is preferably 140°C to 180°C, more preferably 150°C to 170°C, and even more preferably 160°C to 170°C. In the present invention, the melting point (Tm) can be determined by using a DSC (DSC6200) manufactured by Seiko Instruments Inc., packing 5 mg of pellet-shaped sample pieces into an aluminum pan, heating from room temperature to 200°C at a heating rate of 100°C / min, holding at 200°C for 5 minutes, and then cooling from 200°C to 40°C at a heating rate of 10°C / min to crystallize the sample, determining the maximum crystallization peak temperature (°C) as the crystallization temperature (Tc), and then heating from 40°C to 200°C at a heating rate of 10°C / min to melt the sample, determining the maximum melting peak temperature (°C) as the melting point (Tm). The pellet-shaped sample can be obtained by melt-kneading the resin using a granulator, withdrawing the molten resin extruded from a strand die while cooling and fixing it in a cooling water tank, and cutting the strands using a strand cutter.

[0090] The melting point (Tm) is adjusted by the content of comonomers other than propylene monomers during propylene polymerization. The more propylene monomers are added, the higher the melting point (Tm), with propylene homopolymers having the highest melting point. On the other hand, the more comonomers other than propylene are added, the lower the melting point (Tm). Therefore, the melting point (Tm) of the polypropylene resin (Y) can be adjusted by adjusting the type and content of comonomers other than propylene monomers.

[0091] 2-2. Manufacturing method of polypropylene resin (Y) The polymerization catalyst for producing the polypropylene resin (Y) may be a Ziegler-Natta catalyst and / or a metallocene catalyst, but may also be another catalyst. Ziegler-Natta catalysts are described in Section 2.3.1 (pages 20-57) of "Polypropylene Handbook," edited by Edward P. Moore Jr., translated and supervised by Yasuda Tetsuo and Sakuma Nobuo, Kogyo Chosakai (1998). Ziegler-Natta catalysts include (1) titanium trichloride catalysts consisting of titanium trichloride and organoaluminum halide, magnesium chloride, titanium halide, (2) magnesium-supported catalysts consisting of solid catalyst components containing electron donor compounds, organoaluminum and organosilicon compounds, and (3) catalysts combining organoaluminum compound components with organosilicon-treated solid catalyst components formed by contacting solid catalyst components with organoaluminum and organosilicon compounds.

[0092] The metallocene catalyst includes a catalyst in combination with (i) a metallocene compound, (ii) a co-catalyst capable of being activated to a stable ionic state by reacting with the metallocene compound, and (iii) an organoaluminum compound. In order to improve the mechanical properties of the polypropylene resin (Y), the metallocene compound used to synthesize the polypropylene resin (Y) is preferably a crosslinked metallocene compound capable of stereoregular polymerization of propylene, and more preferably a crosslinked metallocene compound capable of isoregular polymerization of propylene.

[0093] Examples of the metallocene compound (i) include those described in JP-A-60-35007, JP-A-61-130314, JP-A-63-295607, JP-A-1-275609, JP-A-2-41303, JP-A-2-131488, JP-A-2-76887, JP-A-3-163088, JP-A-4-300887, JP-A-4-211694, JP-A-5-43616, JP-A-5-209013, JP-A-6-239914, JP-T-H7-504934 and JP-A-8-85708.

[0094] Specific examples of the metallocene compound (i) include: Methylenebis(2-methylindenyl)zirconium dichloride, Ethylenebis(2-methylindenyl)zirconium dichloride, Ethylene 1,2-(4-phenylindenyl)(2-methyl-4-phenyl-4H-azulenyl)zirconium dichloride, Isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(4-methylcyclopentadienyl)(3-t-butylindenyl)zirconium dichloride, Dimethylsilylene(2-methyl-4-t-butyl-cyclopentadienyl)(3'-t-butyl-5'-methyl-cyclopentadienyl)zirconium dichloride, Dimethylsilylenebis(indenyl)zirconium dichloride, Dimethylsilylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[4-(1-phenyl-3-methylindenyl)]zirconium dichloride, Dimethylsilylene(fluorenyl) t-butylamido zirconium dichloride, Methylphenylsilylenebis[1-(2-methyl-4-(1-naphthyl)-indenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4,5-benzoindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenyl-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-naphthyl-4H-azulenyl)]zirconium dichloride, Diphenylsilylenebis[1-(2-methyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(3-fluorobiphenylyl)-4H-azulenyl)]zirconium dichloride, Dimethylgermylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, and Dimethylgermylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride and the like zirconium compounds.

[0095] The metallocene compound (i) in which the zirconium is replaced with titanium or hafnium, and / or a mixture thereof, can also be used as a polymerization catalyst for producing a polypropylene resin (Y). The metallocene compound (i) in which the chloride is replaced with other halogen compounds, hydrocarbon groups such as methyl, isobutyl, and benzyl, amide groups such as dimethylamide and diethylamide, alkoxide groups such as methoxy and phenoxy, and hydride groups can also be used as a polymerization catalyst for producing a polypropylene resin (Y).

[0096] In order to improve the moldability of a resin composition containing a polypropylene-based resin (Y), the metallocene compound (i) which is a polymerization catalyst for producing the polypropylene-based resin (Y) is preferably a metallocene compound in which an indenyl group or an azulenyl group is crosslinked with a silicon or germyl group.

[0097] The polymerization catalyst for producing the polypropylene-based resin (Y) may be supported on an inorganic or organic compound. In order to improve the production amount of the polypropylene-based resin (Y), the support is preferably porous. The support is preferably an inorganic compound such as ion-exchangeable layered silicate, zeolite, SiO2, Al2O3, silica alumina, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, etc., an organic compound such as porous polyolefin, styrene-divinylbenzene copolymer, olefin-acrylic acid copolymer, etc., or a mixture thereof.

[0098] In order to improve the production amount of the polypropylene resin (Y), it is preferable to use a co-catalyst together with the metallocene compound. The co-catalyst is preferably an organoaluminum oxy-compound such as an aluminoxane compound, an ion-exchangeable layered silicate, a Lewis acid, a boron-containing compound, an ionic compound, or a fluorine-containing organic compound.

[0099] In order to improve the productivity of the polypropylene resin (Y), the organoaluminum compound (iii) is preferably a trialkylaluminum such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum or trioctylaluminum, a dialkylaluminum halide, an alkylaluminum sesquihalide, an alkylaluminum dihalide, diethylaluminum chloride, ethylaluminum chloride, diethylaluminum ethoxide, methylalumoxane, an alkylaluminum hydride or an organoaluminum alkoxide.

[0100] In order to improve the production efficiency of the polypropylene resin, the production method of the polypropylene resin (Y) is preferably a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. For the production of polypropylene and propylene random copolymers, a multi-stage polymerization method such as a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. can be used.

[0101] When additives are mixed with the polypropylene-based resin (Y), the polypropylene-based resin (Y) may be produced by mixing together with necessary additives using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender, etc. The polypropylene-based resin (Y) may be produced by kneading using a kneading machine such as a single-screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer.

[0102] The polypropylene resin (Y) may be in the form of a powder, particles, etc. The particles of the polypropylene resin (Y) include granulated products of the polypropylene resin (Y).

[0103] 3. Polypropylene resin composition The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing a branched polypropylene resin (X) and a polypropylene resin (Y) in a specific ratio described in detail below. The polypropylene resin composition of the present invention contains a branched polypropylene resin (X) in an amount of 1% by mass to 80% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y), from the viewpoints of processability in high-speed inflation and transparency of the film produced by high-speed inflation. The content of the branched polypropylene resin (X) may be 5% by mass or more, 10% by mass or more, 20% by mass or more, or 30% by mass or more, relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may be 70% by mass or less, or 50% by mass or less. In addition, the polypropylene resin composition of the present invention contains 20% by mass to 99% by mass of polypropylene resin (Y) relative to 100% by mass of the total mass of the resin (X) and the resin (Y), from the viewpoints of processability in high-speed inflation and transparency of the film by high-speed inflation. The content of polypropylene resin (Y) may be 30% by mass or more, or 50% by mass or more, relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may be 95% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.

[0104] The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing the branched polypropylene resin (X) and the polypropylene resin (Y) as essential components, and may further contain other components such as additives and other polymers different from the branched polypropylene resin (X) and the polypropylene resin (Y).

[0105] 3-1.Additives The polypropylene resin composition of the present invention may further contain additives as necessary in addition to the branched polypropylene resin (X) and polypropylene resin (Y). By appropriately selecting the additives, the functions of the polypropylene resin composition can be improved. The additives may be used alone or in combination of two or more. The additives include, for example, at least one selected from the group consisting of antioxidants, lubricants, antistatic agents, antiblocking agents, UV absorbers, light stabilizers, and neutralizing agents.

[0106] Examples of the antioxidant include phenol-based stabilizers such as 2,6-di-t-butyl-p-cresol, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane and n-octadecyl-3-(4'-hydroxy-3,5'-di-t-butylphenyl)propionate, and phosphite-based stabilizers such as bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite and tris(2,4-di-t-butylphenyl)phosphite. Examples of the lubricant include higher fatty acid amides and higher fatty acid esters. Examples of the antistatic agent include glycerin esters, sorbitan acid esters, and polyethylene glycol esters of fatty acids having 8 to 22 carbon atoms. Examples of anti-blocking agents include silica, calcium carbonate, and talc.

[0107] Furthermore, by incorporating an ultraviolet absorber and a light stabilizer in the polypropylene resin composition, the weather resistance of the polypropylene resin composition can be improved. Examples of the ultraviolet absorbent include compounds having an absorption band in the ultraviolet region, such as triazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, salicylate-based ultraviolet absorbents, cyanoacrylate-based ultraviolet absorbents, nickel chelate-based ultraviolet absorbents, inorganic fine particle-based ultraviolet absorbents, etc. Among these, triazole-based ultraviolet absorbents are a typical example. Examples of triazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-amylphenyl)benzotriazole, and 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole. Benzophenone-based ultraviolet absorbents include, for example, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, and the like. An example of the salicylate-based ultraviolet absorber is 4-t-butylphenyl salicylate. An example of a cyanoacrylate-based ultraviolet absorber is ethyl (3,3-diphenyl) cyanoacrylate. An example of the nickel chelate ultraviolet absorber is nickel dibutyldithiocarbamate. Examples of inorganic particulate ultraviolet absorbents include TiO2, ZnO2, and CeO2.

[0108] Typical light stabilizers include compounds having a hindered amine skeleton (hereinafter referred to as "HALS"). HALS includes sebacate type compounds, butanetetracarboxylate type compounds, succinic acid polyester type compounds, triazine type compounds, and the like. Examples of the sebacate type compound include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and the like. Examples of butane tetracarboxylate type compounds include tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, a condensate of 1,2,3,4-butane tetracarboxylic acid with 2,2,6,6-tetramethyl-4-piperidinol and tridecyl alcohol, and a condensate of 1,2,3,4-butane tetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and tridecyl alcohol. An example of the succinic acid polyester type compound is a condensation polymer of succinic acid and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine. Examples of triazine-type compounds include N,N'-bis(3-aminopropyl)ethylenediamine·2,4-bis{N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino}-6-chloro-1,3,5-triazine condensate, poly{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino, and poly(6-morpholino-s-triazine-2,4-diyl){(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino.

[0109] In the polypropylene resin composition of the present invention, the total content of the additives is not particularly limited as long as it is appropriately selected according to the properties of the additives. In the polypropylene resin composition of the present invention, the upper limit of the total content of the additives may be, for example, 10 parts by mass or less, 1 part by mass or less, or 0.5 parts by mass or less, and the lower limit may be 0 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the polypropylene resin (Y).

[0110] 3-2.Other polymers The polypropylene resin composition of the present invention may further contain other polymers as necessary in addition to the above-mentioned branched polypropylene resin (X) and polypropylene resin (Y). The other polymers can improve the performance or adjust the properties of the branched polypropylene resin composition as modifiers in the polypropylene resin composition. Examples of the other polymers used as modifiers include, but are not limited to, elastomers, polyethylene resins, etc. Examples of the elastomer include ethylene-α-olefin copolymers, binary random copolymer resins of propylene and an α-olefin having 4 to 12 carbon atoms, and ternary random copolymer resins of propylene, ethylene, and an α-olefin having 4 to 12 carbon atoms. Examples of styrene-based elastomers include hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-vinylated polyisoprene block copolymers, and hydrogenated styrene-butadiene random copolymers.

[0111] Examples of polyethylene resins include ethylene / α-olefin copolymers such as low-density polyethylene and linear low-density polyethylene, and their density is 0.860 g / cm. 3 ~0.910g / cm 3 and preferably in the range of 0.870 g / cm 3 ~0.905g / cm 3More preferably, it is 0.875 g / cm 3 ~0.895g / cm 3 If the content exceeds the above range, the transparency may decrease. The density is a value measured at 23° C. in accordance with JIS K7112. The α-olefin used in the ethylene / α-olefin copolymer is preferably an α-olefin having 3 to 18 carbon atoms. Specific examples include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, 4,4-dimethylpentene-1, etc. The α-olefin may be one type or a combination of two or more types. Examples of such ethylene / α-olefin copolymers include ethylene-based elastomers, ethylene-propylene-based rubbers, etc. In particular, ethylene / α-olefin copolymers called metallocene-based polyethylenes, which are produced using metallocene-based catalysts with little loss of transparency, are preferred.

[0112] In the polypropylene resin composition of the present invention, the total content of the other polymers is not particularly limited as long as the effect is not impaired and may be appropriately selected according to the purpose. The upper limit of the total content of the other polymers may be, for example, 50 parts by mass or less, 30 parts by mass or less, or 10 parts by mass or less, and the lower limit may be 0 parts by mass, but may be 1 part by mass or more, or 3 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the polypropylene resin (Y).

[0113] The polypropylene resin composition of the present invention is prepared by blending 100 parts by mass of the branched polypropylene resin (X) and the polypropylene resin (Y) in total, or other components that do not impair the effects of the present invention, as required. Examples of the method for mixing these components include a method of mixing using a Henschel mixer, V blender, ribbon blender, tumbler blender, etc., and a method of melt-kneading using a kneader such as a single-screw extruder, multi-screw extruder, kneader, or Banbury mixer, as required. In either case, there is no particular limitation on the mixing method as long as the effects of the present invention are not impaired.

[0114] 4. Characteristics of polypropylene resin composition The polypropylene resin composition of the present invention may have a melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg of 0.1 g / 10 min to 50 g / 10 min, preferably 0.1 g / 10 min to 30 g / 10 min, and more preferably 1 g / 10 min to 10 g / 10 min, from the viewpoints of processability in an inflation method of the polypropylene resin composition and transparency and strength of the film.

[0115] In the polypropylene resin composition of the present invention, from the viewpoints of transparency and strength of the inflation film, the melting point (Tm) measured by differential scanning calorimetry is preferably 140°C to 180°C, more preferably 150°C to 170°C, and even more preferably 160°C to 170°C. In the polypropylene resin composition of the present invention, from the viewpoints of transparency and strength of the inflation film, the crystallization temperature (Tc) measured by differential scanning calorimetry is preferably 100°C to 140°C, more preferably 110°C to 130°C, and even more preferably 120°C to 130°C.

[0116] From the viewpoint of increasing strength, the polypropylene resin composition of the present invention may have a melt tension at 230° C. (MT230) of 0.1 g to 5 g, or 0.3 g to 4 g.

[0117] 5. Uses of polypropylene resin compositions The polypropylene resin composition of the present invention contains a branched polypropylene resin (X) and a polypropylene resin (Y) and has improved high-speed stretching properties during molding, and is therefore particularly suitable for use in inflation molding. Thus, the polypropylene resin composition of the present invention is a branched polypropylene resin composition for inflation films.

[0118] 6. Method for producing polypropylene resin composition The polypropylene resin composition of the present invention can be produced by blending, mixing, and melt-kneading the branched polypropylene resin (X), the polypropylene resin (Y), and additives used as necessary in the above-mentioned content ratios by a conventionally known method.

[0119] The polypropylene resin composition of the present invention can be mixed by dry blending using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender or the like. In addition, when producing the composition by melt-kneading and granulation, the above-mentioned mixture of components may be kneaded at the same time. Furthermore, in order to improve the performance, each component may be divided and kneaded separately, that is, for example, a method may be adopted in which a part of the components to be used is first kneaded, and then the remaining components are kneaded and granulated.

[0120] The polypropylene resin composition of the present invention is preferably produced by dry blending the components to be used. As a preferred embodiment of the method for producing a polypropylene-based resin composition of the present invention, a branched polypropylene-based resin (X) having the above-mentioned properties (X-1) to (X-4) and and a polypropylene resin (Y) having the above-mentioned characteristic (Y-1). By mixing the branched polypropylene resin (X) and the polypropylene resin (Y) by dry blending, it is possible to uniformly mix them in a relatively short time at low cost, and stable performance can be obtained. The resulting mixture is usually melt-kneaded as described above.

[0121] II. Blown Film and Film Manufacturing Method 1. Blown film The inflation film of the present invention comprises the polypropylene resin composition of the present invention. The blown film of the present invention includes an air-cooled blown film, a water-cooled blown film, and a blown film produced by cooling with other media. The inflation film of the present invention is made of the polypropylene resin composition of the present invention, and thus has good film strength while being improved in film transparency, surface roughness, or a combination of these.

[0122] The thickness of the inflation film of the present invention is not particularly limited and may be appropriately selected depending on the application. The thickness of the film is usually 1 μm to 250 μm, may be 3 μm to 200 μm, or may be 5 μm to 150 μm.

[0123] The inflation film of the present invention has excellent transparency, and the total haze is preferably 60% or less, more preferably 50% or less. The smaller the total haze value (unit: %), the more preferable it is in terms of excellent transparency. In the present invention, the total haze is measured in accordance with JIS K7136:2000.

[0124] The inflation film of the present invention has reduced surface roughness, and the surface roughness Rz of at least one of the outer and inner surfaces is preferably 2.0 μm or less, more preferably 1.5 μm or less. The outer surface roughness Rz of the inflation film of the present invention may be 2.0 μm or less, or may be 1.5 μm or less, and the surface roughness Rz of both the outer and inner surfaces is preferably 2.0 μm or less, more preferably 1.5 μm or less. The smaller the surface roughness Rz value, the less uneven the film surface is, and the less likely light is to be diffusely reflected on the film surface. For this reason, prints on films with small Rz are easier to see clearly, creating a sense of luxury for the film print. The smaller the surface roughness Rz value, the less uneven the film surface is, which has the advantage that dust and other particles are less likely to adhere to the film surface. In the present invention, the surface roughness Rz refers to the maximum height Rz measured in accordance with JIS B0601:2013, and is measured using a shape analysis laser microscope (Keyence, VK-X200). Here, the measurements are performed with Rmr at 50% of the reference mr, Rmr(c) at a cut level of 10 μm and 50%, Rc at 25% of the reference mr, and comparison mr at 75%.

[0125] The inflation film of the present invention is also excellent in strength, and the Young's modulus in both the direction horizontal to the film-forming direction (MD) and the direction perpendicular to the film-forming direction (TD) is preferably 1800 MPa or more, more preferably 2000 MPa or more. In the present invention, Young's modulus is measured in accordance with JIS K 7127: 1999. The higher the Young's modulus value, the higher the strength.

[0126] As described above, the inflation film of the present invention has high transparency, and therefore can be used to package optical equipment by taking advantage of the transparency. However, the performance of these optical equipment may change due to dimensional changes caused by heat absorption. This change in performance of the optical equipment is caused by absorption of infrared light by dust of about 1 to 5 μm attached to the packaging film of the optical equipment. In contrast, optical equipment packaged with the inflation film of the present invention has a small surface roughness Rz of the film, so dust that absorbs infrared light is less likely to adhere to the film. Therefore, the inflation film of the present invention can prevent changes in the performance of the packaged optical equipment. In particular, an inflation film having a surface roughness Rz of 2.0 μm or less, and further 1.5 μm or less, is less likely to have dust particles of about 1 to 5 μm adhered thereto. Therefore, the inflation film of the present invention having such a surface roughness can prevent changes in the performance of the optical equipment packaged therein.

[0127] The inflation film of the present invention may be a single layer film or a multilayer film. In the case of a multilayer film, for example, a two-layer inflation film containing the polypropylene resin composition of the present invention in one layer and another polyolefin resin in the other layer, a two-layer inflation film containing the polypropylene resin composition of the present invention in one layer and the polypropylene resin composition of the present invention in a different composition ratio in the other layer, etc. can be mentioned. Such an inflation film is excellent in stability and transparency during high-speed inflation molding. Similarly, for a film having three or more layers, the stability and transparency during high-speed inflation molding are improved by disposing the polypropylene resin composition of the present invention in at least one layer. For the other layers, a suitable polyolefin resin or polyolefin resin composition can be used depending on the required physical properties of the final film.

[0128] 2. Film manufacturing method The method for producing a film made of the polypropylene resin composition of the present invention is an inflation method. The method for producing a polypropylene-based resin film of the present invention includes a step of forming a film from the polypropylene-based resin composition of the present invention by an inflation method.

[0129] From the viewpoint of workability such as small-lot multi-item production and continuous product changeover, the film is preferably formed by the inflation method by melting the polypropylene resin composition of the present invention using an extruder equipped with an annular die to form a tube, extruding the molten tubular resin (bubbles) into a tube, blowing air supplied from a blower or the like through an air-cooling ring onto the molten tubular resin (bubbles) to cool and solidify it, passing through a guide plate, folding it with pinch rolls, and taking it up with a take-up machine.

[0130] In the production of a film by air-cooled inflation molding, the die diameter is typically φ50 mm to φ500 mm, and the die lip width is typically 0.8 mm to 4.0 mm. From the viewpoint of design such as film transparency and productivity such as stable continuous molding, the molding temperature is preferably 170 to 250° C., more preferably 170 to 220° C. In the present invention, the homogeneity of the film is improved by suppressing bubble vibration during inflation molding, and molding can be performed at a high speed, for example, at a molding speed of 5 to 100 m / min, preferably 10 to 50 m / min.

[0131] The inflation molding method includes air-cooled inflation, water-cooled inflation and tubular biaxial stretching, but from the viewpoint of production equipment cost and workability, air-cooled inflation is preferred. In the inflation molding process, the film is cooled from the outside and / or the inside of the tubular film.

[0132] The blowing method for the tubular film includes an upward type, a horizontal type, a downward type, etc. In order to reduce the cost and size of the manufacturing equipment and to improve the productivity such as the efficiency of cooling the film, the blowing method for the tubular film is preferably a film-forming method in the upward direction.

[0133] The film (inflation film) made of the polypropylene resin composition of the present invention produced as described above has a small Rz, which is an index of surface roughness, and therefore the film surface is less uneven, so that diffuse reflection of light is unlikely to occur on the film surface. Therefore, printed matter on the film (inflation film) made of the polypropylene resin composition of the present invention is easily visible, and the film print has a high-quality feel. Therefore, the film (blowing film) made of the polypropylene resin composition of the present invention can be used as a packaging film or packaging material as it is.

[0134] The film (inflation film) made of the polypropylene resin composition of the present invention can be laminated with other layers depending on the application. The other layers can be made of resin, paper, metal, leather, etc. depending on the required physical properties of the final application of the film.

[0135] III. Packaging The packaging body of the present invention is characterized by including the inflation film of the present invention. The package of the present invention may be, for example, a bag made by heat-sealing films (blowing films) made of a polypropylene resin composition together. Examples of the form of the package include a palm-sealed bag, a three-sided sealed bag, a four-sided sealed bag, a gusseted bag, a stand-up bag, and bags with zippers for these bags. The packaging body of the present invention can be used for packaging, for example, beverages, foods, medicines, cosmetics, stationery, daily necessities, clothing, electronic parts, optical equipment, etc. In particular, since the film can produce a luxurious printed appearance, it is suitable for applications such as bread packaging, stationery packaging, daily necessities packaging, etc. In particular, since dust and the like are less likely to adhere to the film surface, it is also suitable for packaging electronic parts, optical equipment, etc. EXAMPLES

[0136] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following examples, the autoclave was thoroughly dried in advance by passing nitrogen through it under heating before use, and the catalyst preparation and polymerization were all carried out under an inert gas. In the present embodiment, the term "MD" refers to the direction in which the film is fed during extrusion molding, and the term "TD" refers to the direction perpendicular to the direction in which the film is fed during extrusion molding and parallel to the film surface.

[0137] I. Measurement and Evaluation Methods The following (1) to (16) were measured and calculated by the methods described in this specification. (1) MFR Furthermore, the measured MFR value was used to calculate the right-hand sides of the above formulas (1), (2) and (7). (2) Mw / Mn and Mz / Mw obtained by GPC (3) W1 million, W2 million, and W2 million / W1 million in the integral molecular weight distribution curve obtained by GPC (4) g' (million), g' (Mw abs ), and [g'(Mw abs )-g'(1 million)] (5) Ea in dynamic viscoelasticity measurement (6) 13 mm, [2,1 bond] amount, and [1,3 bond] amount measured by C-NMR (7) 13 LCB number measured by C-NMR (8) SHI@1.0s obtained from extensional viscosity measurement -1 and MBI (9) Melt tension (MT230) (10) MaxDraw (11) [Vi], terminal vinyl ratio, number of LCBs / ([Vi]+number of LCBs) (12) Melting point (Tm)

[0138] (13) Total haze (unit: %) (14)Young’s modulus The Young's modulus of the film in the MD direction is referred to as "Young's modulus (MD)" and the Young's modulus of the film in the TD direction is referred to as "Young's modulus (TD)". (15) Surface roughness (Rz) The outer surface roughness of the inflation film is referred to as "Rz (outer surface)".

[0139] (16) Heat shrinkage rate Measure the heat shrinkage of the film in accordance with JIS Z 1712:2009. Measure also when the temperature of the standard, 120℃, is changed to 140℃, 160℃, or 180℃. The heat shrinkage rate of the film in the MD direction caused at 120°C for 15 minutes is defined as "HSR120MD". The heat shrinkage rate of the film in the TD direction caused at 120°C for 15 minutes is defined as "HSR120TD". The heat shrinkage rate of the film in the MD direction caused at 140°C for 15 minutes is defined as "HSR140MD". The heat shrinkage rate of the film in the TD direction caused at 140°C for 15 minutes is defined as "HSR140TD". The heat shrinkage rate of the film in the MD direction caused at 160°C for 15 minutes is defined as "HSR160MD". The heat shrinkage rate of the film in the TD direction caused at 160°C for 15 minutes is defined as "HSR160TD". The heat shrinkage rate of the film in the MD direction caused at 180°C for 15 minutes is defined as "HSR180MD". The heat shrinkage rate of the film in the TD direction caused at 180°C for 15 minutes is defined as "HSR180TD". When the film being measured is melted and the heat shrinkage rate cannot be measured, it is recorded as "molten."

[0140] II. Production of polypropylene resin composition and film 1. Branched polypropylene resin (X) 1-1. Production of branched polypropylene resin (X1) (1) Synthesis of catalyst component (A) (1-1) Synthesis Example 1: Synthesis of catalyst component [A-1] (Complex 1) Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium: rac-Dichloro[1,1′-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium was synthesized according to the method of Synthesis Example 1 in JP2012-149160A.

[0141] (1-2) Synthesis Example 2: Synthesis of catalyst component [A-2] (Complex 2) 1) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2): (1-a) Synthesis of 2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene: The synthesis was carried out with reference to the method described in Example 1 of JP-A-2003-517010. (1-b) Synthesis of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane: 2,5-Dimethyl-3-phenyl-hydrocyclopenta[b]thiophene (8.8g, 39mmol) and THF (200ml) were added to a 500ml glass reaction vessel and cooled to -70℃. n-Butyllithium-n-hexane solution (1.55mol / L, 25ml, 39mmol) was added dropwise. After the addition, the mixture was stirred for 2 hours while gradually returning to room temperature. The mixture was cooled again to -70℃, 1-methylimidazole (0.15ml, 1.9mmol) was added, and a THF solution (30ml) containing dimethyldichlorosilane (2.5g, 19mmol) was added dropwise. After the addition, the mixture was stirred overnight while gradually returning to room temperature. Distilled water was added to the reaction solution obtained, which was then transferred to a separatory funnel and washed with saline until neutral. Sodium sulfate was added and the reaction solution was left overnight to dry. The sodium sulfate was filtered off, the solvent was removed under reduced pressure, and the resulting solid was purified using a silica gel column to obtain a white powder of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (9.8 g, 99% yield). (1-c) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex A): Dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (6.1g, 12mmol) and 200ml of diethyl ether were added to a 500ml glass reaction vessel, and the vessel was cooled to -70℃ in a dry ice-methanol bath. A n-butyllithium-n-hexane solution (1.55mol / L, 16ml, 24mmol) was added dropwise to the vessel. After the addition, the mixture was returned to room temperature and stirred for 2 hours. The solvent of the reaction solution obtained was concentrated under reduced pressure to about 20ml, after which 250ml of toluene and 10ml of THF were added, and the mixture was cooled to -70℃ in a dry ice-methanol bath. 3.8g (12mmol) of hafnium tetrachloride was added to the vessel. The mixture was then gradually returned to room temperature and stirred overnight. The solvent was distilled off under reduced pressure and the resulting solid was recrystallized from toluene / hexane to obtain 0.87 g (yield 10%) of racemic dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (purity 97%) as yellow crystals.

[0142] The racemic mixture was analyzed by proton nuclear magnetic resonance ( 1 The identified values ​​by H-NMR are shown below. 1 H-NMR (CDCl3) Identification Results Racemic: δ1.06(s,6H), δ2.42(s,6H), δ2.59(s,6H), δ8.51(s,2H), δ7.28~δ7.33(m,2H), δ7.39~δ7.43(m,4H), δ7.46~δ7.50(m,4H)

[0143] (2) Synthesis example of component (B): Chemical treatment of ion-exchangeable layered silicate Into a 1 L three-neck flask equipped with a stirring blade and a reflux device, 645.1 g of distilled water and 82.6 g of 98% sulfuric acid were added and heated to 95°C. 100 g of commercially available montmorillonite (Benclay KK manufactured by Mizusawa Chemical Industry Co., Ltd., Al=9.78% by mass, Si=31.79% by mass, Mg=3.18% by mass, Al / Si (molar ratio)=0.320, average particle size 14 μm) was added thereto, and the mixture was reacted for 320 minutes at 95° C. After 320 minutes, 0.5 L of distilled water was added to stop the reaction, and 255 g of a cake-like solid was obtained by filtration. This cake (1 g) contained 0.31 g of the chemically treated montmorillonite (intermediate). The chemical composition of the chemically treated montmorillonite (intermediate) was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, and Al / Si (molar ratio) = 0.222. 1545g of distilled water was added to the cake to make a slurry, and the temperature was raised to 40℃. 5.734g of lithium hydroxide hydrate was added as a solid to the slurry, and the reaction was carried out at 40℃ for 1 hour. After 1 hour, the reaction slurry was filtered and washed three times with 1L of distilled water, and a cake-like solid was obtained again. The cake-like solid obtained was pre-dried overnight at 90°C or higher under normal pressure, and then dried under reduced pressure for 2 hours or more after the bumping subsided using an oil bath at 200°C to obtain 80 g of chemically treated montmorillonite. The chemical composition of this chemically treated montmorillonite was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, Al / Si (molar ratio) = 0.222, Li = 0.53 mass%.

[0144] (3) Preparation of catalyst 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (45 μmol) prepared in the synthesis example of the catalyst component [A-2] was dissolved in toluene (9 mL) to prepare solution 2.

[0145] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above-mentioned solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Thereafter, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was further added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 28.2 g of a prepolymerized catalyst (Catalyst 1). The prepolymerization ratio (value obtained by dividing the amount of prepolymerized polymer by the amount of solid catalyst) was 1.82.

[0146] (4) Polymerization The 20 L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7 mL of a heptane solution of triisobutylaluminum (140 mg / mL) and 5,000 g of liquid propylene were introduced into the polymerization tank, and the temperature was raised to 63°C. Then, 700 mg of the above catalyst 1 (excluding the prepolymerized polymer) was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature inside the tank was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1,687 g of propylene homopolymer was obtained. The obtained polymer was used for GPC, 3D-GPC, 13 C-NMR measurements were performed.

[0147] (5) Production of branched polypropylene resin pellets (X1) (granulation) 100 parts by mass of the obtained branched polypropylene resin (X) was blended with 0.125 parts by mass of a phenolic antioxidant IRGANOX1010 (manufactured by BASF Japan, tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane) and 0.125 parts by mass of a phosphite antioxidant IRGAFOS168 (manufactured by BASF Japan, tris(2,4-di-t-butylphenyl)phosphite) and mixed for 3 minutes at room temperature using a high-speed stirring mixer (Henschel mixer, manufactured by Nippon Coke & Co., Ltd.). Then, using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.), the screw rotation speed was 400 rpm and the kneading temperature was 80, 120, and 230 ° C. from the bottom of the hopper (the same temperature from then until the die outlet). The molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter. The MFR of the obtained pellets was 4.5 g / 10 min. The evaluation results of each property are shown in Table 1.

[0148] 1-2. Production of branched polypropylene resin (X2) Polymerization was carried out in the same manner as in the polymerization for producing the branched polypropylene resin (X1), except that the catalyst 1 was introduced in an amount of 500 mg (excluding the prepolymerized polymer) and 0.09 NL of hydrogen was introduced. As a result, 1750 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 9.0 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0149] 1-3. Production of branched polypropylene resin (X3) Polymerization was carried out in the same manner as in the polymerization for producing the branched polypropylene resin (X1), except that the catalyst 1 was introduced in an amount of 400 mg (excluding the prepolymerized polymer) and 0.43 NL of hydrogen was introduced. As a result, 2109 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 21 g / 10 min. The properties were evaluated in the same manner as in Example 1, and the results are shown in Table 1.

[0150] [Reference: Production of branched polypropylene resin] <Reference: Production of branched polypropylene resin (CX1)> (1) Preparation of catalyst (1-1) Synthesis of comparative catalyst component [CA-2] Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium: rac-Dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) was synthesized according to the method of Example 7 of JP-A-11-240909.

[0151] (1-2) Synthesis example of catalyst 2 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (45 μmol) prepared in the synthesis example of the comparative catalyst component [CA-2] was dissolved in toluene (9 mL) to prepare solution 2.

[0152] Triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added to a 1 L flask containing the above-mentioned chemically treated montmorillonite, and then the above-mentioned solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Thereafter, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was further added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 30.9% prepolymerized catalyst (catalyst 2). The prepolymerization rate was 2.09%.

[0153] (2) Polymerization and granulation The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) and 0.68NL of hydrogen were introduced into the polymerization tank, followed by 5000g of liquid propylene, and the temperature was raised to 63°C. Then, 310mg of the catalyst 2, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the inside of the tank was quickly heated to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 2288g of propylene homopolymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 3.3 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0154] <Reference: Production of branched polypropylene resin (CX2)> Polymerization was carried out in the same manner as in the polymerization for producing the reference branched polypropylene resin (CX1), except that 230 mg of catalyst 2 (excluding the prepolymerized polymer) and 1.02 NL of hydrogen were introduced. As a result, 1978 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 9.9 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0155] <Reference: Production of branched polypropylene resin (CX3)> Polymerization was carried out in the same manner as in the polymerization for producing the reference branched polypropylene resin (CX1), except that 220 mg of catalyst 2 (excluding the prepolymerized polymer) and 1.11 NL of hydrogen were introduced. As a result, 1936 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 15.0 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0156] [Table 1]

[0157] FIG. 2 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for the branched polypropylene resins (X1) to (X3) used in the present invention and the reference branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 4 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for the branched polypropylene resins (X1) to (X3) used in the present invention and the reference branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum winding speed (MaxDraw) at 230° C., and data for the branched polypropylene resins (X1) to (X3) used in the present invention and the reference branched polypropylene resins (CX1) to (CX3) are plotted.

[0158] 2. Polypropylene resin (Y) As the polypropylene resin (Y), the following polypropylene resins (Y1) to (Y2) were prepared. Polypropylene resin (Y1): Made by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) FL4", MFR = 4 g / 10 min, Tm = 164°C, g' (million) = 1.00 Polypropylene resin (Y2): manufactured by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) SA4L", MFR = 6 g / 10 min, Tm = 161°C, g' (million) = 1.00

[0159] 3. Production of polypropylene resin composition and film production [Examples 1 to 4 and Comparative Examples 1 to 2] (1) Production of polypropylene resin composition Pellets (X2) of branched polypropylene resin (X) and pellets (Y1) to (Y2) of polypropylene resin (Y) in the amounts shown in Table 2 were put into a high-speed stirring mixer and stirred for 3 minutes to obtain mixed pellets. The amounts shown in Table 2 are shown in mass % relative to the total mass of the resin (X) and the resin (Y), which is 100 mass %. Regarding the pellets used in measuring the MFR of the polypropylene resin composition, the mixed pellets were further melt-kneaded using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.) at a screw rotation speed of 400 rpm and kneading temperatures of 80, 120, and 230°C (the same temperature from the bottom of the hopper to the die outlet), and the molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter.

[0160] [Table 2]

[0161] (2) Blown film manufacturing The mixed pellets of the polypropylene resin composition obtained above were extruded under the conditions of an extruder temperature of 220°C, annular die temperature of 230°C, and a discharge rate of 7.5 kg / h, and an air-cooled inflation film with a single layer of 30 μm was obtained under the conditions of a film folding width of 500 mm (blow ratio of 1.6) and a take-up speed of 10 m / min. The physical properties of the obtained inflation film are shown in Table 3.

[0162] [Table 3]

[0163] From Examples 1 to 4 and Comparative Examples 1 and 2, it was shown that the polypropylene resin composition of the present invention, which contains a branched polypropylene resin (X) having a branched polypropylene structure different from conventional ones in combination with a polypropylene resin (Y), improves the transparency and surface roughness of a film produced by inflation molding without impairing the strength of the film.

[0164] The performance evaluation for preparing a catalyst for producing the branched polypropylene resin (X) of the present invention is shown below. [Reference Example 1]: Performance evaluation of complex 1 as catalyst component (A) (Preparation of Catalyst R1) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (65 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 35 mL of heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (0.15 mmol) synthesized in Synthesis Example 1 was dissolved in toluene (30 mL) to prepare a solution.

[0165] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 40 minutes to obtain 29.5 g of a prepolymerized catalyst (Catalyst R1). The prepolymerization rate was 1.95.

[0166] (polymerization) The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) and 0.51NL of hydrogen were introduced into the polymerization tank, followed by 5000g of liquid propylene, and the temperature was raised to 63°C. Then, 300mg of the catalyst R1, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1740g of propylene homopolymer was obtained. Table 2 shows the results of MFR, GPC, and NMR measurements using the obtained polymer.

[0167] [Reference Example 2]: Performance evaluation of complex 2 as catalyst component (A) (Preparation of Catalyst R2) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (0.15 mmol) synthesized in Synthesis Example 2 was dissolved in toluene (30 mL) to prepare a solution.

[0168] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 32.0 g of a prepolymerized catalyst (Catalyst R2). The prepolymerization rate was 2.20.

[0169] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R2 was used instead of catalyst R1, 100 mg of the mass excluding the prepolymerized polymer, and 1.19 NL of hydrogen was introduced. As a result, 1153 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 2.

[0170] [Reference Example 3]: Performance evaluation of complex 3 as catalyst component (A) (Preparation of catalyst R3) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (0.15 mmol) synthesized in Synthesis Example 3 was dissolved in toluene (30 mL) to prepare a solution.

[0171] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 31.0 g of a prepolymerized catalyst (Catalyst R3). The prepolymerization rate was 2.10.

[0172] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R3 was used instead of catalyst R1, 300 mg of the mass excluding the prepolymerized polymer, and 0.51 NL of hydrogen was introduced. As a result, 1570 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 4.

[0173] From the results of Reference Examples 1 to 3 in Table 4, it was shown that complex 1 can be used as a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is performed at 70°C using component [A-1], and complex 2 can be used as a metallocene compound that gives a propylene homopolymer a-2 having a number average molecular weight (Mn) larger than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and smaller than 0.5 when propylene homopolymerization is performed at 70°C using component [A-2], and the propylene homopolymer a-2 can be used as a metallocene compound in which the ratio of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is larger than that of the propylene homopolymer a-1. Complex 3 was a metallocene compound that gave a propylene homopolymer having a larger Mn than the propylene homopolymer a-1 but an Rv of 0 when propylene homopolymer was subjected to propylene homopolymerization at 70°C.

[0174] [Table 4]

Claims

1. A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following properties (Y-1) to (Y-2), A polypropylene-based resin composition for an inflation film, comprising 1% by mass to 80% by mass of the resin (X) and 20% by mass to 99% by mass of the resin (Y), relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.

0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.60 to 0.

75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. Characteristic (Y-2): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.95 or more.

2. The polypropylene-based resin composition according to claim 1, wherein the polypropylene-based resin (Y) is a homopolymer of propylene.

3. A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A method for producing a polypropylene-based resin composition for an inflation film, comprising the step of dry-blending a polypropylene-based resin (Y) having the following properties (Y-1) to (Y-2): Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.

0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.60 to 0.

75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. Characteristic (Y-2): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.95 or more.

4. An inflation film comprising the polypropylene resin composition according to claim 1 or 2.

5. A method for producing a film, comprising a step of molding the polypropylene resin composition according to claim 1 or 2 by an inflation method.

6. The method for producing a film according to claim 5 , wherein the inflation method is an air-cooled inflation method.

7. A package comprising the inflation film of claim 4.

Citation Information

Patent Citations

  • Air-cooled inflation molded polypropylene film

    JP2004182967A

  • Polypropylene resin composition for molding inflation film and method of manufacturing film

    JP2014132068A